2011
DOI: 10.1371/journal.pone.0026235
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 and TLR8 Gene Variations and Susceptibility to Hepatitis C Virus Infection

Abstract: Toll-like receptors (TLRs) play pivotal roles in the innate immune system and control inflammatory responses and adaptive immunity. We previously evaluated associations between TLR7 and TLR8 gene SNPs and susceptibility to hepatitis C virus (HCV) infection. Our results suggested that TLR7IVS2-151G and TLR8-129G alleles were present at higher frequency in males of an HCV-infected group as compared to a control group (24.1% vs. 14.4%, p = 0.028; 17.6% vs. 6.8%, p = 0.004, respectively). Based upon their recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 31 publications
(43 reference statements)
6
68
2
Order By: Relevance
“…It has been suggested that they play important roles in induction by IFN and inflammatory cytokines [14,15]. Based on data from our laboratory we have demonstrated that TLR7 and TLR8 polymorphisms influence TLR7 and TLR8 expression and signal transduction upon ligand stimulation [16,17]. We previously identified a single nucleotide polymorphism (SNP) at IVS2-151 in TLR7 (rs179009), and disequilibrium association of TLR8 with a SNP resulting in a Met/Val change at a start codon associated (G/C) SNP (rs3764879) at position -129 of the promoter [18].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been suggested that they play important roles in induction by IFN and inflammatory cytokines [14,15]. Based on data from our laboratory we have demonstrated that TLR7 and TLR8 polymorphisms influence TLR7 and TLR8 expression and signal transduction upon ligand stimulation [16,17]. We previously identified a single nucleotide polymorphism (SNP) at IVS2-151 in TLR7 (rs179009), and disequilibrium association of TLR8 with a SNP resulting in a Met/Val change at a start codon associated (G/C) SNP (rs3764879) at position -129 of the promoter [18].…”
Section: Introductionmentioning
confidence: 87%
“…The percentage of monocytes expressing TLR7 and TLR8 was significantly lower in subjects with the TLR7 IVS2-151A/TLR8-129G haplotype, but higher in intensity compared to cells from those with the TLR7 IVS2-151A/TLR8-129C haplotypes. Cells from MANUSCRIPT 4 subjects with the TLR7 IVS2-151A/TLR8 -129G haplotype produced more IFN-α and less pro-inflammatory cytokines upon stimulation [17]. A large number of studies have investigated the influence of TLR gene polymorphisms on MTB susceptibility [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…TLR7 and TLR8 are innate receptors for single-stranded viral RNA. They have been associated with susceptibility to hepatitis C (Wang et al, 2011a), which may play a favoring role in CD (see below). The genetic link with innate antiviral responses seems however less strong in CD than in T1D, in which a combination of GWAS and eQTL data has revealed an association with a whole network of antiviral innate immune genes (Foxman and Iwasaki, 2011).…”
Section: Loss Of Tolerance and Tissue Damage In Cd: A Need For Additimentioning
confidence: 99%
“…TLR8 gene is located on chromosome X, which is known to house the largest number of immune-related genes of the whole genome (Bianchi et al, 2012). Single nucleotide polymorphisms (SNPs) located within TLR8 have been related with an altered innate immune response, susceptibility to HCV infection (Wang et al, 2011;Wang et al, 2013), and progression of HIV disease (Mackelprang et al, 2014;Oh et al, 2008). HCV may also directly activate the innate immune system via TLR8, leading to chronic inflammation and hepatic fibrosis; and may impair TLR signaling in order to evade clearance and promote chronic infection (Howell et al, 2013).…”
Section: Chronic Hepatitis C (Chc) Represents a Leading Comorbidity Imentioning
confidence: 99%